Flamboyant sexual signals: multiple messages for multiple receivers. (May 2017) - Zambre, Amod M.; Thaker, Maria
Abstract : Animals are often faced with the challenge of signalling to multiple receivers that might differ in their detection abilities and preferences. Such conditions are expected to favour the evolution of complex signals. The superb fan-throated lizard, Sarada superba, possesses one of the most complex sexual trait of any lizard: an enlarged dewlap with blue, black and orange patches that is flapped rapidly during both courtship and aggressive displays. We examined the use of the tricoloured dewlap in social signalling to determine whether (1) movement enhances signal detection, and whether (2) males and females differ in their preference for colours. Using robotic lizard stimuli, we measured receiver responses to movement and colour individually, and found that movement attracted both sexes, but the latency to respond was faster when dewlaps had all three colours compared to none (white). Furthermore, the sexes did not differ in the ability to detect colours, as more than 80% of lizards preferred coloured to white dewlaps. Most strikingly, however, the sexes showed strong preferences for different colours. Females preferentially responded to orange colour on dewlaps, and males responded to blue and black, indicating that different colours are targeted at different receivers. These results highlight that complex signals can evolve due to simultaneous inter- and intrasexual selection. Highlights: Male S. superba use a flapping tricoloured dewlap during social interactions. Using moving robot stimuli, we found that flapping attracts both sexes. Females choose orange and males choose blue and black. This signal attracts attention by moving and conveys multiple messages with colour.